Research Trends on Students Engagement in EFL Classroom: A Literature Analysis on Online Scientific Publication from 2020-2023 - Saleh, Yuwin Rustam; Darwis, Nirwana (Journal of English Teaching and Linguistic Issues (JETLI), 2024)
This bibliometric analysis examines research trends on students’ engagement in EFL classrooms from 2020 to 2023, revealing substantial academic interest with a total of 982 publications. The analysis highlights a peak in publications in 2022, underscoring the growing emphasis on student-centered teaching approaches. However, citation metrics show a significant decline over the years, indicating a shift in scholarly attention and citation behavior. The study also identifies a marked disparity in author influence, with the top 20 authors contributing to a significant portion of the citations. Keyword analysis and network visualization using VOSviewer reveal a strong focus on themes like online learning, student engagement, and the impact of the COVID-19 pandemic. These findings suggest that while the field is expanding, there is a need for ongoing research to address emerging challenges and sustain academic impact. This study contributes to understanding the dynamic landscape of EFL education, providing insights for future research and practice.